Manajemen Pemeliharaan Peralatan Berbasis Web - Rasyidah; Asraf (SOTVI - Society of Visual Informatics, 2023)
The Teluk Sirih Power Plant (PLTU), owned by PT. PLN (Persero) in West Sumatra, utilizes coal as its primary energy source. Located in Teluk Sirih Village, Padang City, with two units each generating 112 MW of power, routine maintenance is pivotal in maintaining the electricity production performance. Understanding work instructions, Occupational Health and Safety (K3) policies, and maintenance-related information is of paramount importance to ensure efficient maintenance practices. However, during visits and interviews, it was revealed that there are differences in understanding work instructions, K3 policies, and maintenance-related information between experienced and new employees, which can impede maintenance activities. The research titled